Revision of the Palaearctic species of Eupelmus (Eupelmus) Dalman (Hymenoptera: Chalcidoidea: Eupelmidae) - Gibson, Gary A. P.; Fusu, Lucian (Zootaxa, 2016)
One hundred-four extant species of Eupelmus Dalman (Hymenoptera: Eupelmidae: Eupelminae) are recognized from the Palaearctic region, of which 76 species of E. (Eupelmus) are recognized following a revision of the Palaearctic fauna of the subgenus. The following 25 species are described as new: E. (Eupelmus) adustus Gibson & Fusu n. sp., E. (Eupelmus) angustifrons Gibson & Fusu n. sp., E. (Eupelmus) bicolor Gibson & Fusu n. sp., E. (Eupelmus) brachypterus Fusu & Gibson n. sp., E. (Eupelmus) brachystylus Gibson & Fusu n. sp., E. (Eupelmus) brachyurus Fusu & Gibson n. sp., E. (Eupelmus) fasciatus Gibson & Fusu n. sp., E. (Eupelmus) gelechiphagus Gibson & Fusu n. sp., E. (Eupelmus) hayei Gibson & Fusu n. sp., E. (Eupelmus) infimbriatus Gibson & Fusu n. sp., E. (Eupelmus) iris Fusu & Gibson n. sp., E. (Eupelmus) kamijoi Gibson & Fusu n. sp., E. (Eupelmus) lanceolatus Gibson & Fusu n. sp., E. (Eupelmus) luteipes Fusu & Gibson n. sp., E. (Eupelmus) magdalenae Fusu & Gibson n. sp., E. (Eupelmus) mehrnejadi Gibson & Fusu n. sp., E. (Eupelmus) melanostylus Gibson & Fusu n. sp., E. (Eupelmus) punctatifrons Fusu & Gibson n. sp., E. (Eupelmus) setosus Fusu & Gibson n. sp., E. (Eupelmus) tanystylus Gibson & Fusu n. sp., E. (Eupelmus) tetrazostus Gibson & Fusu n. sp., E. (Eupelmus) vanharteni Fusu & Gibson n. sp., E. (Eupelmus) weilli Fusu & Gibson n. sp., E. (Eupelmus) xenium Fusu & Gibson n. sp., and E. (Eupelmus) zebra Fusu & Gibson n. sp. Of previously described species of Eupelmus, 17 are newly assigned to E. (Eupelmus), 10 to E. (Episolindelia Girault), and 8 to E. (Macroneura Walker). Formally transferred to E. (Macroneura) from Macroneura are E. (M.) algiricus (Kalina 1981), E. (M.) coleophorae (Kalina 1981), E. (M.) impennis (Nikol’skaya 1952), E. (M.) longicornis (Kalina 1981), E. (M.) pleuratus (Kalina 1981) and E. (M.) sugonyaevi (Kalina 1981) n. combs. Eupelmus (Eupelmus) kalinai Gibson & Fusu n. name is given to replace E. (Eupelmus) algiricus Kalina 1988, a secondary homonym of E. (M.) algiricus (Kalina 1981). New synonyms proposed are Eupelmus scolyti Liao 1987 n. syn. under E. (Eupelmus) formosae Ashmead 1904, and Eupelmus nigricauda Nikol’skaya 1952 n. syn. under E. (Eupelmus) microzonus Förster 1860. Eupelmus gueneei Giraud 1870 and Eupelmus xambeui Giard 1900 are transferred to Arachnophaga (Parasolindenia Brues) as A. (P.) gueneei (Giraud) and A. (P.) xambeui (Giard) n. combs., and Eupelmus kim Nikol’skaya 1952 is transferred to Brasema Cameron as B. kim (Nikol’skaya) n. comb. Eupelmus puparum Newport 1840 is transferred to Pteromalus Swederus (Pteromalidae) as P. puparum (Newport) n. comb., a secondary homonym of P. puparum (Linnaeus 1758), and Ceraphron brachynterae Schwägrichen 1835 is removed from Eupelmus and Eupelmidae, and the name treated as incertae sedis. Lectotypes are designated for Eupelmus azureus Ratzeburg 1844, Pteromalus cordairii Ratzeburg 1844, Eupelmus hostilis Förster 1860, and Eupelmus splendens Giraud 1872. Neotypes are designated for Pteromalus audouinii Ratzeburg 1844 and Eupelmus bedeguaris Ratzeburg 1852. Newly recorded from the Palaearctic are E. (Eupelmus) orthopterae (Risbec 1951) and E. (Eupelmus) peculiaris Narendran (2011). Excluded from the Palaearctic are E. (Eupelmus) afer Silvestri 1914 (Afrotropical) and E. (Eupelmus) longicorpus (Girault 1915) (Australasian), the former being compared to E. confusus Al khatib 2015 and the latter to E. iranicus Kalina 1988 and E. kalinai. Seven informal species groups are recognized for the purpose of species comparisons, the fulgens-, fulvipes-, iranicus-, orientalis-, splendens-, stramineipes-, and urozonus-groups. The latter group is restricted to E. urozonus Dalman and five other species that were differentiated initially using molecular evidence. Females of all 76 species of E. (Eupelmus) recognized from the Palaearctic are keyed, described and illustrated. Males are recognized for 44 of the species, and keyed and illustrated, though not all males of the fulvipes- and urozonus-groups are distinguished from each other.